Paradoxality of Women Positions in Othello by Shakespeare - Siti Hardiyanti Amri; Isna Maylani (JELITA, 2020)
This research studied about the positions of female characters in the play Othello by Shakespeare. By applying the intersectional concept of Chandra Mohanty, the research identified that the women positions were determined by the aspects of race and class. The high-class woman in patriarchal system was subordinated by lower class man due to gender relation. Meanwhile the research also exhibited that women could have strong domination toward men in regard to race relation. It asserted the intersect relation of race, class, and gender. In this case, under certain circumstances, women were not always positioned inferior toward men and men did not always have ultimate power on women. The relation of both gender in the novel indicated that other aspects such as race and class also played the significant role in determining the position of each.